(NoSNOWY PROEKTIROWANIQ I STROITELXSTWA NA MAKROPORISTYH GRUNTAH (B/s - (NaBELEW(B, (N`(B.(Nm(B.s; (NtOKARX(B, (Nr(B.(Na(B.s ((NlENINGRAD (B:s (NsTROJWOENMORIZDAT(B,s, 1948)
(NzAKL(B. : (NS(B. 199-200s
(NpODSTR(B. (NPRIME^(B.s
(NlIT(B. : (NS(B. 201-203s
Keywords: (NmAKROPORISTYE GRUNTYs -- (NPROEKTIROWANIEs